Viability and Infectivity of Plasmodium vivax Gametocytes in Short-Term Culture - Ramos, Glenda Quaresma; Baia-da-Silva, Djane Clarys; Lacerda, Marcus Vinícius Guimarães; Monteiro, Wuelton Marcelo; Lopes, Stefanie Costa Pinto (Frontiers in Cellular and Infection Microbiology, 2021)
The control and elimination of malaria caused by Plasmodium vivax both represent a great challenge due to the biological aspects of the species. Gametocytes are the forms responsible for the transmission of the parasite to the vector and the search for new strategies for blocking transmission are essential in a scenario of control and elimination The challenges in this search in regard to P. vivax mainly stem from the lack of a long-term culture and the limitation of studies of gametocytes. This study evaluated the viability and infectivity of P. vivax gametocytes in short-term culture. The samples enriched in gametocytes using Percoll (i), using magnetic-activated cell sorting (MACS®) (ii), and using non-enriched samples (iii) were evaluated. After the procedures, gametocytes were cultured in IMDM medium for up to 48 h. Cultured P. vivax gametocytes were viable and infectious for up to 48 h, however differences in viability and infectivity were observed in the samples after 12 h of culture in relation to 0 h. Percoll-enriched samples were shown to be viable in culture for longer intervals than those purified using MACS®. Gametocyte viability after enrichment procedures and short-term culture may provide new avenues in the development of methods for evaluating P. vivax TB.